PS-BPB09-8: ANGIOTENSIN RECEPTOR BLOCKER AMELIORATES ELEVATED ARTERIAL BLOOD PRESSURE AND REDUCES BODY MASS IN OLETF RATS FED A HIGH CHOLESTEROL DIET. (January 2023) - Jardines, Eira Edith; Rodriguez, Ruben; Minas, Jacqueline; Nakano, Daisuke; Nishiyama, Akira; Ortiz, Rudy M
Abstract : Objective: Cardiovascular disease (CVD) is the leading cause of death in the US (1 in 4) and is a primary outcome of Metabolic Syndrome (MetS). MetS affects nearly 40% of adults over 60 and is defined by a cluster of conditions including elevated arterial pressure and excess abdominal fat. A high cholesterol diet (HCD) is known to promote cluster-factor conditions of MetS. Unfortunately, body mass (BM) reduction is often insufficient to reduce hypertension. The first line of pharmaceutical defense is disruption of the renin-angiotensin aldosterone system (RAS). Inappropriate elevation of RAS can be therapeutically attenuated with angiotensin receptor blocker (ARBs), which has been shown to ameliorate other MetS cluster factor conditions. However, the efficacy of ARB on elevated arterial pressure during a HCD remains unclear. Design: A cohort of 5-week-old Otsuka Long Evan Tokushima Fatty (OLETF) rats were fed a HCD (2% + 0.5% cholic acid) or chow ad libitium. After 4 weeks, animals were treated with ARB (10 mg olmesartan /kg/d x 3 wks by oral gavage) and assigned to five groups: 1) lean-strain control Long Tokushima Evans Otsuka (LETO; n = 10), 2) OLETF (OLETF; n = 12), 3) OLETF+HCD (n = 12), 4) OLETF+ARB (n = 12) and 5) OLETF+HCD+ARB (n = 12). Systolic blood pressure was monitored chronically by radio telemetery. Results: OLETF SBP was 31% (p < 0.05) greater than LETO. HCD did not exacerbate elevated SBP in OLETF. ARB reduced SBP in OLETF + HCD by 11% (p < 0.05) over 30 days and 13% (p < 0.05) overall compared to OLETF. ARB reduced BM by 3% (p < 0.05) in chow-fed and 4% (p < 0.05) in HCD-fed OLETF compared to OLETF. However, there was no difference in BM between OLETF+ARB and OLETF+HCD+ARB. Neither, HCD nor ARB alone reduced abdominal fat in OLETF rats. ARB in OLETF+HCD induced visceral fat loss (37%; p < 0.05) compared to OLETF. ARB administration did not attenuate plasma angiotensin II levels. Conclusion: These findings demonstrate that chronic treatment with ARB can effectively ameliorate the MetS-associated hypertension despite the additional insult of a HCD.